2014
DOI: 10.4067/s0717-95022014000200009
|View full text |Cite
|
Sign up to set email alerts
|

Supraorbital Notch/Foramen in Sri Lankan Skulls: Morphometry and Surgical Relevance

Abstract: SUMMARY:Evidence supports the ethnic and sex variation in the form and position of the supraorbital foramen. Therefore, detailed knowledge of the population specific data on biometric features of the supraorbital foramen will facilitate diagnostic, local anesthetic and surgical manipulations in the maxillo-facial region. The goal of this study was to elucidate the morphological features and precise anatomical position of the supraorbital foramen with reference to surrounding surgically encountered anatomical l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…while SOF in 26% [3,6,13,14,15,25,29]. However, Thunyacharoen et al [22] and Woo et al [29] found a higher incidence of SOF than SON.…”
Section: Discussionmentioning
confidence: 96%
“…while SOF in 26% [3,6,13,14,15,25,29]. However, Thunyacharoen et al [22] and Woo et al [29] found a higher incidence of SOF than SON.…”
Section: Discussionmentioning
confidence: 96%
“…A fairly comprehensive anatomical knowledge on the SOF/N is necessary in flap reconstructions used in upper eyelid lift surgeries (blepharoplasty) and forehead surgeries. The frequency of the occurrence of SOF/ N in the shape of foramen and notch varies considerably in different populations (Rehman et al, 2012;Tomaszewska et al, 2012;Ilayperuma et al, 2014). Symmetry is an indication of beauty and attractiveness in the human face and there are many studies on sex and age-related changes in the face (Ferrario et al, 1994;Ferrario et al, 2001;Baudouin & Tiberghien, 2004;Zaidel & Cohen, 2005).…”
Section: Introductionmentioning
confidence: 99%